Toughness characteristics of Arenga pinnata fibre concrete - Razak, H.A.; Ferdiansyah, T. (2005)
This paper reports the results of an investigation on the toughness characteristics of concrete containing Arenga pinnata fibre. Three fibre lengths of 15 mm, 25 mm, and 35 mm were used in two volume fractions, i.e., 0.6 and 0.8. The values of toughness, first crack deflection, first crack toughness, toughness indices, and residual strength factors are presented for ages up to 180 days. It was observed that the addition of Arenga pinnata fibre increased the toughness characteristic of concrete. However, it was observed that the positive effects of the fibre become less significant after 28 days, but still sufficient to give the concrete better toughness properties compared to the plain concrete.This is due to reaction of the fibres with the alkaline pore water in the cement matrix. Â© 2005 by The Haworth Press, Inc. All rights reserved.